Good Deeds Could Come From Frustrated Individuals - Peng, Yibo; Tang, Jinghua; Li, Hanzhou (Frontiers in Psychology, 2021)
Frustration is often seen as negative, but as to whether it may have a positive impact on the individual is still undecided. This research was conducted to explore the influence of frustration on altruistic tendency and altruistic level in college students (17–21 years old). By presenting a highly difficult task combined with negative feedback, we effectively induced frustration in Experiment 1 (n = 70). By assessing the donation behavior of participants (n = 54) in a real-life scenario following the experimental manipulation of frustration, we examined the relationship between frustration and altruism in Experiment 2. Results showed that frustrating situations could, on some level, improve altruistic behavior [t(8.834) = 3.013, p = 0.015]. More specifically, among participants who donated, the amount donated was higher in the frustration group compared to the control (fulfillment) group; the proportion of people who donated did not differ by group.